Професійна спрямованість фізико-математичної підготовки студентів нематематичних спеціальностей - Дзямко Вікторія; Месарош Лівіа; Dzуamko Viсtoria; Livia Mesarosh; Dzámko Viktória; Mészáros Lívia (Ужгородський національний університет, 2017)
Резюме. У статті розкрито методичні прийоми навчання вищої математики і фізики студентів нематематичних спеціальностей. Без фундаментальної фізико-математичної підготовки неможлива сучасна якісна економічна, технічна, інженерна, біологічна, хімічна освіта. На прикладі розв’язування задач професійноорієнтованого змісту, наведено способи реалізації прикладної й професійної спрямованості фізико-математичного курсу для майбутніх фахівців-нематематиків.

Резюме. В статье раскрыты методические прийомы обучения высшей математики и физики студентов нематематических специальностей. Без фундаментальной физико-математической подготовки невозможно современное качественное економическое, техническое, инженерное, биологическое, химическое образование. На примере решения задач профессионально-ориентированного содержания, приведены способы реализации прикладной и профессиональной направленности физико-математического курса для будущих специалистов-нематематиков.

Abstract. The article considers the methodical approaches towards teaching higher mathematics and physics to students of non-mathematical specialties. The aim of the article is to reveal methodological approaches of teaching nonmathematical specialties students the higher mathematics and physics of applied and professional character. To achieve the aim of the article the following tasks have been defined: 1) to analyze the state of the problem in the methodological literature, as well as in the practice of training specialists in the Transcarpathian Hungarian Institute named after Ferenc Rakoci II; 2) to analyze branch standards, educational and professional programmes, educational qualifications, curricula on the higher mathematics and physics in order to identify interdisciplinary connections; 3) to determine the place, role and significance of mathematics and physics, physical and mathematical methods when solving professional problems by specialists of the profile; 4) to identify ways and methods for implementing the applied and professionally directed character of physical and mathematical course for future professionals − nonmathematicians; 5) to improve the appropriate methods, forms and means of realization of professional direction in the educational process.
Профессиональная направленность физико-математической подготовки студентов нематематических специальностей
Professionally directed physical-mathematical training of students of non-mathematical specialties
Keywords: професійна спрямованість; фізико-математичні науки; нематематичні спеціальності; профессиональная направленность; физико-математические науки; нематематические специальности; professional direction; physical and mathematical sciences; nonmathematicians